Strategi Prinsip Ekonomi Islam dalam Meningkatkan Ketahanan Ekonomi Keluarga Muslim Di Kabupaten Demak - Lia Sari, Risti (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research aims to find out the principles of Islamic Economics in increasing the economic resilience of Muslim families in Demak Regensy and to find out what strategies the principles of Islamic Economics have in creasing the economic resilience of Muslim in Demak Regency. The Urgency or priority of this research was carried out in the hope that the Islamic Economic Principles strategy could help in increasing the economic resilience of Muslim families in Demak Regency. Tools / Intruments This research is a type of field research with qualitative research methods. The result of thisresearch are the principles of Islamic Economics in increasing the economic resilience of Muslim families in Demak Regency, including by balancing sources of incoming and asset ownership, estabilishing cooperation or syirkah, equitable social security, the role of government Keywords : Islamic Economic, Principles, family economic security